Green tea and its potential benefits for health - Sarani Ali Abadi, parvaneh; Nasrabadi, tahereh; Etemadi, suodabeh (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim Technology and development in the field of health and treatment has been lead to the production and delivery of synthetic drugs and chemical compounds in this field, But because of low efficacy and undesirable side effects some of these drugs are considered as a potential threat to human health. There fore this nutritional approach and use of herbal medicines has been common in many countries. Green tea that is the most common be average in the world and especially in East Asia (China - Japan) is known as one of the powerful antioxidants due to having poly phenolic flavonoid compounds. Evidences show that so far, experimental studies (clinical) have been done on small scale animal and human samples to verify the therapeutic properties of polyphenols compounds of green tea. The purpose of this paper is to provide the therapeutic effects of green tea that are confirmed at different researches. Materials and methods To achieve researches and studies related to the effects of green tea, these sites were investigated:" Medline, Irandoc, Elsevier, scpous, pubmed scholar, by using the following keywords "tea, green tea, flavonoids, catechin, obesity, hyperlipidemia, hyperglycmic (diabetes), stroke, vascular heart, cancer and depression, and totally 55 articles from 2000 to 2010 were reviewed and summarized. Findings The results of these studies have introduced the green tea, as a matter of anti-inflammatory, anticancer, anti cholesterol, anti-diabetic, anti-mutation, anti-microbial, anti-stroke and so on. It is also proved to be effective in genital warts. In addition bioactive components of green tea (catechin and caffeine) stimulates the sympathetic system resulting in increased heat production and fat oxidation in the body and in this way they perform their anti-obesity function. Conclusion According to the results of the studies, it appears that green tea is as a low-risk supplement treatment for certain diseases and health problems and is considered as the most common safe drink, but further researches are necessary to examine its effects. Key words: Green tea, Benefits, Health, Research of review. *Corresponding Author: Lecturer, Islamic Azad University, Zahedan Branch, Zahedan, Iran. E-mail: spsarani@yahoo.com - Alexopoulos N et al (2010). Role of green tea in reduction of cardiovascular risk factors.Nutrition and Dietary Supplements. 11 (2) 85-95. -Arab L Liuw Elashoff D (2009).Green and black tea consumption and risk of stroke: Ameta-analysis. Stroke.40(1) 1786-1792. -Basu A et al (2010). Green tea supplementation affects body weight, lipid and lipid peroxidation in obese subjects with metabolic syndrome. Journal of the American College of Nutrition. 29 (1) 31-40. -Bettuzzi S et al (2006). A chemo prevention of human prostate cancer by oral administration of green tea catechin in volunteers with high-grade prostat intraepithelial neoplasia: A preliminary report from a one – year proof –of –principle study. Cancer Research. 66 (2) 1234-1240. -Brown Al et al (2009). Effect of dietary supplementation with the green tea polyphenol epigallatechin -3-gallate on insulin resistance and associated metabolic risk factors: randomized controlled trail.British Journal Nutrition.101(6)886- 894. -Bose M et al (2008). The major green tea polyphenol (-) epigallo catechin -3 - gallate inhibits obesity metabolic syndrome and fatty liver disease in high –fat-fed mice. The Journal of Nutrition. 138 (9) 1677-1683. -Chad E et al (2010). Green tea polyphenol epigallocate chin gallate reduces endothelin-1 expressionand secretion in vascular endothelial cells.Endocrinology.151(1) 103-114. -Chen Z et al (2004). A study on the association between tea consumption and stroke.Zhonghua liu Xing Bing Xue Za Zhi. 25 (8) 666-670. -Choan E et al (2005). A pros pective clinical trial of green tea for hormone refrancetory prostate cancer: an evaluation of the complementary /alternative therapy approach. Urol Oncol. 23 (2) 108-113. -Craig S Tiffany S (2009).Green Tea: Potential healt benefits. American Family Physicion.79 (7) 591-594. -DiePvens K et al (2005). Effect of green tea on resting eneygy expenditure and sabstate oxidation during Weight loss in oVerWeight Females. British Journal Nutrition. 94 (4) 1026-1034. -DiePvens K et al (2006). Metabolic Effects of green ea and of phases of Weight looSS. Physiol Behav. 87(1) 185-191. -Erba D et al (2005). Effectiveness of moderate green tea consumption on antioxidative status and plasma lipid profile in humans.Journal Nurtion Biochem.16 (1) 144-49. -Fukino Y et al (2005). Randomized controlled trial foran effect of green tea consumption on insulin resistance and inflammation markers.Journal Nutr Sci Vitaminol. 51 (1) 335-342. -Hininger-Favier I et al (2009). Green tea extract Decreases oxidative stress and improves Insulin sensitivity in an animal model of Insulin resistance, the fructose –fed rat. Journal of the American College of Nutrition. 28 (4) 355-361. -HuaHsu C et al (2008). EFFect of green tea extract on obese Women : A randomized , double blind , PlaCebo _ controlled clinical trial. Clinical Nutrition. 27 (3) 363-370. -Iwai N et al (2002). Relationship between coffe and green tea consumption and all-cause mortality in a cohort of a rural Japanese population.Journal Epidemiol. 12 (3) 191-198. -Iwaniec UT et al (2009). Consumption of green tea extract results in osteopenia in growing male mice. The American Institute of Nutrition. 139 (10) 1914-1919. -Josic J et al (2010). Dose green tea affect postprandial glucose,insulin and satiety in healthy subjects : arandom ized controlled trial.Nutrition Journal. 30 (9) 63-70. -Jung C et al (2006). Associations between two single nucleotide polymorphisms of adiponectin gene coronarg arterg diseases.Endocrine Journal. 53 (1) 671-7. -Karaca T et al (2010). Effects of extract of green tea and ginseng on pancreatic Beta cells and levels of serum glucose, Insulin, cholesterol and triglycerides in rats with experimentally Streptozotocin – Induced diabetes. Journal of Animal and Veterinary Advances. 9 (1) 102-107. -Kajiya K et al (2008). Solid-state NMR analysis of the orientation and dgnamics of epigallocatechin gallate a green tea polgphenol incorporated into lipid bilayers.Magnetic Resonance chemistry. 46 (2) 174-7. - Alexopoulos N et al (2010). Role of green tea in reduction of cardiovascular risk factors.Nutrition and Dietary Supplements. 11 (2) 85-95. -Arab L Liuw Elashoff D (2009).Green and black tea consumption and risk of stroke: Ameta-analysis. Stroke.40(1) 1786-1792. -Basu A et al (2010). Green tea supplementation affects body weight, lipid and lipid peroxidation in obese subjects with metabolic syndrome. Journal of the American College of Nutrition. 29 (1) 31-40. -Bettuzzi S et al (2006). A chemo prevention of human prostate cancer by oral administration of green tea catechin in volunteers with high-grade prostat intraepithelial neoplasia: A preliminary report from a one – year proof –of –principle study. Cancer Research. 66 (2) 1234-1240. -Brown Al et al (2009). Effect of dietary supplementation with the green tea polyphenol epigallatechin -3-gallate on insulin resistance and associated metabolic risk factors: randomized controlled trail.British Journal Nutrition.101(6)886- 894. -Bose M et al (2008). The major green tea polyphenol (-) epigallo catechin -3 - gallate inhibits obesity metabolic syndrome and fatty liver disease in high –fat-fed mice. The Journal of Nutrition. 138 (9) 1677-1683. -Chad E et al (2010). Green tea polyphenol epigallocate chin gallate reduces endothelin-1 expressionand secretion in vascular endothelial cells.Endocrinology.151(1) 103-114. -Chen Z et al (2004). A study on the association between tea consumption and stroke.Zhonghua liu Xing Bing Xue Za Zhi. 25 (8) 666-670. -Choan E et al (2005). A pros pective clinical trial of green tea for hormone refrancetory prostate cancer: an evaluation of the complementary /alternative therapy approach. Urol Oncol. 23 (2) 108-113. -Craig S Tiffany S (2009).Green Tea: Potential healt benefits. American Family Physicion.79 (7) 591-594. -DiePvens K et al (2005). Effect of green tea on resting eneygy expenditure and sabstate oxidation during Weight loss in oVerWeight Females. British Journal Nutrition. 94 (4) 1026-1034. -DiePvens K et al (2006). Metabolic Effects of green ea and of phases of Weight looSS. Physiol Behav. 87(1) 185-191. -Erba D et al (2005). Effectiveness of moderate green tea consumption on antioxidative status and plasma lipid profile in humans.Journal Nurtion Biochem.16 (1) 144-49. -Fukino Y et al (2005). Randomized controlled trial foran effect of green tea consumption on insulin resistance and inflammation markers.Journal Nutr Sci Vitaminol. 51 (1) 335-342. -Hininger-Favier I et al (2009). Green tea extract Decreases oxidative stress and improves Insulin sensitivity in an animal model of Insulin resistance, the fructose –fed rat. Journal of the American College of Nutrition. 28 (4) 355-361. -HuaHsu C et al (2008). EFFect of green tea extract on obese Women : A randomized , double blind , PlaCebo _ controlled clinical trial. Clinical Nutrition. 27 (3) 363-370. -Iwai N et al (2002). Relationship between coffe and green tea consumption and all-cause mortality in a cohort of a rural Japanese population.Journal Epidemiol. 12 (3) 191-198. -Iwaniec UT et al (2009). Consumption of green tea extract results in osteopenia in growing male mice. The American Institute of Nutrition. 139 (10) 1914-1919. -Josic J et al (2010). Dose green tea affect postprandial glucose,insulin and satiety in healthy subjects : arandom ized controlled trial.Nutrition Journal. 30 (9) 63-70. -Jung C et al (2006). Associations between two single nucleotide polymorphisms of adiponectin gene coronarg arterg diseases.Endocrine Journal. 53 (1) 671-7. -Karaca T et al (2010). Effects of extract of green tea and ginseng on pancreatic Beta cells and levels of serum glucose, Insulin, cholesterol and triglycerides in rats with experimentally Streptozotocin – Induced diabetes. Journal of Animal and Veterinary Advances. 9 (1) 102-107. -Kajiya K et al (2008). Solid-state NMR analysis of the orientation and dgnamics of epigallocatechin gallate a green tea polgphenol incorporated into lipid bilayers.Magnetic Resonance chemistry. 46 (2) 174-7. -Sun CL et al (2002).Urinary tea polyphenols in relation to gastric and esophageal cancers: prospective study of men in shang –hai china. Carcinogenesis. 23 (9) 1497-1503. -Sutherland B Rahman R Appleton I (2006). Mechanisms of action of green tea catechins with a focus on ischemiainduced neurodegen-eration.Journal Nutrition Biochem. 17 (1) 291-306. -Tanabe N et al (2008). Consumption of green and roasted teas and the risk of stroke Incidence results from the Tokamachi-Nakasato Cohort stady in Japan.Int Journal Epidemiol. 37 (5) 1030-1040. -Taso As et al (2009). Phse II randomized, placebo-controlled trial of green tea extract in patients with high- risk oral premalignant lesions. Cancer Prevention Research. 2 (11) 931-941. -Tokunagas et al (2002). Green tea consumption and serum lipids and lipoproteins in a population of healthy workers in Japan.Ann Epidemiol. 12 (3) 157-165. -Venables MC et al (2008). Green tea extracts ingestion fat oxidation and glucose tolerance in healthy humans. The American Journal of Clinical Nutrition. 87 (3) 778-84. -Vlachopoulos C et al (2003). Caffeine increases aortic stiffness in hypertensive patients.American Journal Hypertens. 16 (1) 63-66. -Westertrep –plantenga MS, Lejeune Mp and kovacs E (2005). Body weight loss and weight maintenance in relation to habitual caffeine intake and green tea supplementation. Obes Res. 13 (7) 1195-204.